2003
DOI: 10.1046/j.1365-2141.2003.04236.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Asian descent on the incidence of acquired severe aplastic anaemia in children

Abstract: Summary. Previous studies have suggested an increased incidence of acquired severe aplastic anaemia in Asian populations. We evaluated the incidence of aplastic anaemia in people of Asian descent, using a well-defined paediatric (0-14 years) population in British Columbia, Canada to minimize environmental factors. The incidence in children of East/South-east Asian descent (6AE9/million/year) and South Asian (East Indian) descent (7AE3/million/year) was higher than for those of White/mixed ethnic descent (1AE7/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…The incidence of AA is highest in patients of Asian descent[21], probably due to increased exposure to environmental toxins and/or genetic polymorphisms involved in the metabolism of these toxins. For the first time, we analyzed both the phase I and phase II xenobiotic metabolizing enzyme loci – the CYP1A1 and GST polymorphisms in patients with AA in India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of AA is highest in patients of Asian descent[21], probably due to increased exposure to environmental toxins and/or genetic polymorphisms involved in the metabolism of these toxins. For the first time, we analyzed both the phase I and phase II xenobiotic metabolizing enzyme loci – the CYP1A1 and GST polymorphisms in patients with AA in India.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a population-based study, it was documented that the incidence of AA in Bangkok was approximately twice as high as in Europe or Israel [20]. Previous reports [21] have suggested that the increased incidence of AA in the Asian population (7.3/million in China and 11/million in Japan and Korea, with a higher incidence especially in girls, 9.8/million/year) may be due to genetic predisposition. Whether the Asian population may have a higher incidence of AA due to susceptible genetic polymorphisms needs to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Primary immune-mediated pathophysiology should be considered in younger patients with morphologic MDS without an increase in myeloblasts in whom paroxysmal nocturnal hemoglobinuria clones can be detected or who are positive for HLA-DR15, 31 and alternative treatments to consider in these patients include aplastic anemia type immunomodulation. There might also be ethnic predispositions to immune-mediated BM failure manifesting as either aplastic anemia or low-risk MDS: aplastic anemia in British Columbia (Canada) is ϳ 4-fold more common among individuals of Asian descent compared with others 42 (presumably the environmental influences are similar among the different ethnic groups in Canada). Further, in east Asian countries, there is more MDS without an increase in myeloblasts occurring in younger individuals, whereas in the west, there is more MDS with increased Figure 1.…”
Section: Patient Selection and Other Treatmentsmentioning
confidence: 99%
“…In a hospital-based study of Canadian pediatric aplastic anemia, a much higher incidence of disease was found in children of Asian descent and correlated to HLA differences, both results by implication favoring genetic rather than environmental risk. 23 In large collaborative studies between the National Cancer Institute and American and Chinese institutions, susceptibility to benzene hematologic toxicity has been correlated to nucleotide polymorphisms in key drug metabolic pathways 24 and to cytokine gene polymorphisms. 25 We can anticipate that the epidemiologic studies of aplastic anemia in the future will reflect this good clinical news and also be more informative of the etiology and pathophysiology of the disease.…”
Section: The Future Of Epidemiologic Studies Of Aplastic Anemiamentioning
confidence: 99%